Food Accessibility as a Determinant of Street Food Purchase Decisions in Lengkong Kecil, Bandung: A Cross-Sectional Study - Muhamad Bagus Mario Khaerudin; Asti Dewi Rahayu Fitrianingsih; Widya Astuti; Isti Kumalasari (Preventif : Jurnal Kesehatan Masyarakat, 2026)
Street food plays a significant role in urban food systems, particularly in developing countries where it provides affordable and accessible meal options for diverse populations. This study examines the determinants of street food purchasing decisions among consumers in Lengkong Kecil, Bandung, a major urban culinary hub that attracts students and low- to middle-income groups. As ready-to-eat food becomes increasingly preferred for its convenience and affordability, understanding the role of food accessibility is critical. While previous studies have primarily focused on hygiene and price, this study highlights the combined influence of physical and economic access as a key determinant of consumer behavior. This study employed a cross-sectional analytical design involving 148 respondents selected through accidental sampling. Participants were consumers aged 18 years and older who purchased street food in the Lengkong Kecil area. Data were collected using structured questionnaires and analyzed using logistic regression.The results showed that perceived food accessibility was the only variable significantly associated with purchasing decisions (p = 0.002; OR = 4.6; 95% CI: 1.7–12.3). Consumers who perceived street food as geographically accessible and economically affordable were significantly more likely to make purchases. Interestingly, although 58.1% of respondents perceived vendor hygiene as poor and 69.6% perceived sanitation as inadequate, these factors did not significantly influence purchasing decisions, highlighting a behavioral paradox in this urban context. In conclusion, food accessibility—defined by both proximity and affordability—plays a dominant role in shaping street food purchasing behavior. Policy and intervention strategies should focus on optimizing vendor placement in high-traffic areas, particularly near student populations, and maintaining affordable price points to better support urban consumers, especially those from low-income groups.